Community Perception of Traditionsas a Mattoana Arajang - Sarifa Suhra; Jumriani Jumriani; Rahmatunnair Rahmatunnair; Suhadi Suhadi; Andi Tahir (Lembaga Sembilan Tiga Community, 2023)
This article presents an exploration of community perceptions surrounding the Arajang tradition as a carpet, with a focus on the Mulamenree Village community in the Ulaweng District, Bone Regency. The research employs a qualitative methodology, grounded in both anthropological and sociological frameworks. Data collection is facilitated through various instruments, including structured interview guides, systematic observation protocols, and documented records. The primary sources of data for this study consist of the Mulamenree Village community members and descendants associated with the Arajang tradition as a carpet. The gathered data are subsequently subjected to a comprehensive qualitative data analysis model, comprising three distinct phases: data reduction, data presentation, and the formulation of substantive conclusions. The research findings illuminate the intricate stages involved in the transformation of Arajang into a carpet within the Mulamenree Village context. These stages include the preparatory phase, the execution of the Arajang tradition as a carpet, and the culmination marked by the ceremonial significance of the Arajang artifact. Moreover, the community's collective perspective on the mattoana Arajang tradition in Mulamenree Village underscores its enduring nature, passed down intergenerationally. Arajang is revered as a sacred and cherished royal relic, with the tradition serving as an essential evidential expression of deep-seated appreciation. The positive impacts stemming from the Arajang tradition encompass enhanced gratitude, an elevated awareness of powers beyond human agency, and the reinforcement of social cohesion. Conversely, potential negative consequences may emerge, such as socioeconomic disparities among participants and the risk of idolatrous behavior when some individuals consider these traditions to surpass their devotion to Allah SWT.